Determinants of a simulated cross-country skiing sprint competition using V2 skating technique on roller skis - Mikkola, J.; Laaksonen, M.; Holmberg, H. C.; Vesterinen, V.; Nummela, A. (The Journal of Strength and Conditioning Research, 2010)
The present study investigated the performance-predicting factors of a simulated cross-country (XC) skiing sprint competition on roller skis, on a slow surface. Sixteen elite male XC skiers performed a simulated sprint competition (4 x 850 m heat with a 20-minute recovery) using V2 skating technique on an indoor tartan track. Heat velocities, oxygen consumption, and peak lactate were measured during or after the heats. Maximal skiing velocity was measured by performing a 30-m speed test. Explosive and maximal force production in the upper body was determined by bench press (BP). Subjects also performed maximal anaerobic skiing test (MAST) and the 2 x 2-km double poling (DP) test. The maximal velocity of MAST (VMAST) and velocities at 3 (V3), 5 (V5), 7 (V7) mmol/L lactate levels in MAST were determined. In the 2 x 2-km test, DP economy (VO2SUBDP) and maximal 2-km DP velocity (VDP2KM) were determined. The best single performance-predicting factors for the sprint performance were VDP2KM (r = 0.73, p < 0.01), V7 (r = 0.70, p < 0.01), and VO2SUBDP (r = -0.70, p < 0.01). Faster skiers in sprint simulation had a higher absolute [latin capital V with dot above]O2 (L/min) (p < 0.05-0.01) during sprint heats, and higher anaerobic skiing power (VMAST, p < 0.05) and better anaerobic skiing economy (V3, V5, V7, p < 0.05-0.001) than slower skiers. Faster skiers were also stronger in BP, with regard to both absolute (p < 0.01) and relative (p < 0.05) values. In addition, anaerobic characteristics seem to be of importance at the beginning of the XC skiing sprint competition, whereas the aerobic characteristics become more important as the XC skiing sprint competition progressed. This study indicates that sprint skiers should emphasize sport-specific upper body training, and training skiing economy at high speeds.